Clinical safety and efficacy of World’s thinnest (50 μm), very long (>40 mm) Everolimus Eluting Stent (SES) among real world patients - Sinha, Santosh Kumar (Am J Cardiovasc Dis, 2020)
Background: Safety and efficacy of newer-generation and World’s thinnest everolimus eluting stent (Evermine 50) in patients with very long and multiple lesions. Method: Total of 711 patients received >40 mm long, World’s thinnest (50 µm) Evermine 50 Everolimus eluting stent (Meril Life Sciences Pvt. Ltd., India) for various indications at LPS Institute of Cardiology, GSVM Medical College, Kanpur, UP, India between August 2017 and December 2018. Primary outcome as Device-oriented composite outcome (DOCO)- composite of cardiovascular death, target vessel myocardial infarction, and target lesion revascularization, secondary end points including peri-procedural device failure (failure of stent delivery, change of stent, edge dissection, stent fracture), target vessel failure (TVF), Global Cardiovascular End Points (GCEP)- composite of all-cause death, any MI, and any revascularization, and stent thrombosis (ST) were evaluated at 1-year follow-up. Result: Mean age was 52.7±15.9 years and majority (78.6%) were male. Indications for implantation were STEMI (n=284; 46.2%), NSTEMI (n=201; 32.8%), UA (n=78; 12.6%), and CCS (n=52; 8.4%). Total of 989 lesions were treated among 711 patients. Median length of stent per lesion was 54±14 mm. DOCO occurred in 47 (6.6%) which was contributed by target vessel MI and TLR in 23 (3.2%) and 15 (2.1%) patients respectively. GCEP was observed in 117 (16.4%) at 12-month follow-up mainly attributed by any revascularization 60 (8.4%). Stent failure was seen in 36 (5.1%) patients mainly as result of failure of assigned stent delivery (n=18; 2.5%), and edge dissection (n=15; 2.1%). Definite and probable ST were observed in 8 (1.1%) and 6 (0.8%) patients respectively. Conclusion: Evermine 50 Everolimus eluting stent is safe and effective to treat unduly long and multiple lesions.